2001
DOI: 10.2337/diabetes.50.1.195
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulation-Induced Increase in Skeletal Muscle Glycogen Synthase Content Is Impaired in Carriers of the Glycogen Synthase XbaI Gene Polymorphism

Abstract: Associations between glycogen synthase gene (GYS1) polymorphism and states of insulin resistance and type 2 diabetes have been reported. The purpose of this study was to establish if the GYS1 genotype impacts on the content of glycogen synthase (GS) protein in muscle measured under basal and stimulated conditions. To examine this, GYS1 XbaI and Met416Val polymorphisms and thigh muscle GYS1 protein content were determined at rest, both before and after several weeks of neuromuscular electrical stimulation in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…When mutations corresponding to several of the alleles found in nature were introduced into enzyme expressed in COS cells, loss of activity was observed. Mutant alleles of GYS1, encoding muscle glycogen synthase, have also been reported and in some cases a correlation with type II diabetes has been suggested [105][106][107] but was not seen in others [108]. Insofar as muscle is an important site of glucose disposal, such a correlation would be reasonable but as yet not fully substantiated.…”
Section: Degradationmentioning
confidence: 89%
“…When mutations corresponding to several of the alleles found in nature were introduced into enzyme expressed in COS cells, loss of activity was observed. Mutant alleles of GYS1, encoding muscle glycogen synthase, have also been reported and in some cases a correlation with type II diabetes has been suggested [105][106][107] but was not seen in others [108]. Insofar as muscle is an important site of glucose disposal, such a correlation would be reasonable but as yet not fully substantiated.…”
Section: Degradationmentioning
confidence: 89%
“…However, it is possible that differences in the GS response could be identified in insulin-resistant subjects by testing the effect of a different exercise challenge. For example, St-Onge et al (41) demonstrated that GS protein content in muscle increases in response to 6 wk of electrical stimulation in subjects that do not carry the XbaI GS polymorphism, whereas muscle contraction does not increase GS content in carriers of this mutation. In the future, it will be interesting to investigate whether abnormalities in GS function can be detected by testing the response to other exercise/contraction protocols.…”
Section: E87 Glycogen Synthase Regulation and Phosphorylation In Diabmentioning
confidence: 99%
“…Interestingly, electrical stimulation of skeletal muscle to mimic physical exercise increased the amount of glycogen synthase in carriers of wild-type C-allele but not in carriers of the T-allele. As a consequence, carriers of the T-allele may benefit less from physical exercise than carriers of the normal allele [11]. GYS1 is located on chromosome 19q13.3, a region that has in several linkage studies been linked to MetS and T2D associated phenotypes [12][17].…”
Section: Introductionmentioning
confidence: 99%